Problematika Interpretasi Hukum "Jangan Berzinah" dalam Keluaran 20:14: Sebuah Landasan Etis bagi Keluarga Kristen - Yanti, Maria Evvy; Mandosir, Glifia Talita (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2022)
Exodus 20:1-17 as the moral and spiritual foundation of the Israelites has many interpretations in its understanding of relevance. Of the many interpretations, there is a tendency to associate it with the law for the violation of sexual behavior between human beings. This interpretation becomes problematic when dealing with the context of the placement of the word in the command sentence. There are dualistic ideas about the understanding of adultery in the Bible from a spiritual and physical perspective. Spiritually adultery is the same as praying for the Lord God or worshipping idols. But physically adultery is shown by sex performed by couples who have not been blessed in marriage. The variety of interpretations of these entities should be viewed in a dynamic position of thought. Therefore this paper shows the entity of adultery based on the analysis of the meaning of the word in the context of its creation taking into account the theological consequences for the present-day reader in the family community. By placing this ethical command in the framework of decalogues, the aspect of fidelity in the marital relationship of a family cannot be separated from fidelity to God.AbstrakKeluaran 20:1-17 sebagai landasan moral dan kerohanian bangsa Israel memiliki banyak penafsiran dalam pemahaman relevansinya. Dari sekian banyak penafsiran terdapat kecenderungan untuk mengaitkannya dengan hukum atas pelanggaran perilaku seksual antara manusia. Penafsiran ini menjadi problematis ketika berhadapan dengan konteks penempatan kata dalam kalimat perintah tersebut. Terdapat gagasan-gagasan dualistis mengenai pemahaman perzinahan di dalam Alkitab dari sisi rohani dan fisik. Secara rohani perzinahan sama dengan menduakan Tuhan Allah atau melakukan penyembahan kepada berhala. Namun secara fisik perzinahan diperlihatkan dengan hubungan seks yang dilakukan oleh pasangan yang belum diberkati dalam pernikahan. Beragam penafsiran entitas ini seharusnya dilihat dalam posisi pemikiran yang dinamis. Oleh karena itu tulisan ini memperlihatkan entitas dari perzinahan berdasarkan analisis makna kata dalam konteks terciptanya dengan mempertimbangkan konsekuensi teologi bagi pembaca masa kini dalam komunitas keluarga. Dengan menempatkan perintah etis ini dalam kerangka dekalog maka aspek kesetiaan dalam relasi pernikahan sebuah keluarga tidak dapat dipisahkan dengan kesetiaan kepada Tuhan.